2021
DOI: 10.3390/geosciences11090373
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Northern Hemisphere Atmospheric Circulation Response to Arctic Ice Reduction Based on Simulation Results

Abstract: The amplified warming of the Arctic is one of several factors influencing atmospheric dynamics. In this work, we consider a series of numerical experiments to identify the role of Arctic sea ice reduction in affecting climate trends in the Northern Hemisphere. With this aim in mind, we use two independent mechanisms of ice reduction. The first is traditionally associated with increasing the concentration of carbon dioxide in the atmosphere from the historic level of 360 ppm to 450 ppm and 600 ppm. This growth … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In addition, the positive North Atlantic Oscillation (NAO) can excite Rossby waves, which can strengthen the Indo-Myanmar trough on the southern side of the plateau and promote snowfall on the QTP, leading to more snow disasters [40,41]. Furthermore, Arctic sea ice, as an important external forcing factor affecting extreme weather and climate events at medium latitudes [42], also has an important modulating effect on the occurrence of snow disasters on the Tibetan plateau. A positive anomaly of Arctic sea ice can enhance the meridional temperature gradient, which excites upward-propagating and equatorward-propagating anomalous Rossby waves, leading to an anomalous dipole pattern of atmospheric circulation over the polar regions and Eurasia, enhancing the zonal advection and meridional convergence of atmospheric moisture fluxes over the plateau and favoring snow disasters [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the positive North Atlantic Oscillation (NAO) can excite Rossby waves, which can strengthen the Indo-Myanmar trough on the southern side of the plateau and promote snowfall on the QTP, leading to more snow disasters [40,41]. Furthermore, Arctic sea ice, as an important external forcing factor affecting extreme weather and climate events at medium latitudes [42], also has an important modulating effect on the occurrence of snow disasters on the Tibetan plateau. A positive anomaly of Arctic sea ice can enhance the meridional temperature gradient, which excites upward-propagating and equatorward-propagating anomalous Rossby waves, leading to an anomalous dipole pattern of atmospheric circulation over the polar regions and Eurasia, enhancing the zonal advection and meridional convergence of atmospheric moisture fluxes over the plateau and favoring snow disasters [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Over long-term scales from November to the subsequent February, the southwestward shift of the upper tropospheric westerly jet may have favored the development of more intense surface cyclones over the TP, which is favorable for heavier snowfall, leading to an increase in snow depth over the TP. However, the interannual variation of snowfall in the TP region is also regulated by the ocean-atmosphere coupling system, such as El Niño-Southern Oscillation (ENSO) and sea-surface temperature (SST), which have an impact on the occurrence of snow disasters [57][58][59]. Furthermore, research has found that as the pure income of herders' families increased and infrastructure such as shelters improved, continuous socioeconomic development led to a decrease in annual livestock losses caused by snow disasters during the period from 1981 to 2015, at the rate of −7% year −1 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies [5][6][7] show that the warming in the Arctic has a significant impact on the winter weather in both North America and East Asia. The authors detail the complex meteorological chain that links these regions to the rotating cold air structure known as the polar vortex or polar cell.…”
Section: Introductionmentioning
confidence: 99%